Nanotechnology-Based Strategies for Safe and Effective Immunotherapy - Seeun Hong; Juwon Park; Yoojeong Oh; Hanhee Cho; Kwangmeyung Kim (Molecules)
Cancer immunotherapy using immune checkpoint blockades has emerged as a promising therapeutic approach. However, immunotherapy faces challenges such as low response rates in solid tumors, necessitating strategies to remodel the immune-suppressive tumor microenvironment (TME) into an immune-activated state. One of the primary approaches to achieve this transformation is through the induction of immunogenic cell death (ICD). Herein, we discussed strategies to maximize ICD induction using nanoparticles. In particular, this review highlighted various studies integrating chemotherapy, radiation therapy (RT), photodynamic therapy (PDT), and photothermal therapy (PTT) with nanoparticle-based immunotherapy. The research covered in this review aims to provide valuable insights for future studies on nanoparticle-assisted immunotherapy.